Comparison of Phytochemical Content and Antifungal Activity of Bajakah Tampala Stem (Spatholobus Littoralis Hassk.) Methanol and Ethanol Extracts Against Candida Albicans - Herdian Fitria Widyanto Putri; Qatrunnada Naqiyyah Khusmitha; Galih Puspita Citra Mahardhika; Dwi Yuni Nur Hidayati; Tri Yudani Mardining Raras; Eviana Norahmawati (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: Candida albicans causes the second most frequent vaginal infection, vulvovaginal candidiasis (VVC). Bajakah Tampala is a natural plant of Kalimantan that has the potential to be used as a traditional remedy for various diseases. This study aims to determine the phytochemical content and antifungal potential of methanol and ethanol Bajakah Tampala stem extract against the growth of Candida albicans. Methods: Flavonoids, tannin, phenol, and saponin were identified through qualitative analysis of the phytochemical content. Different concentration of Bajakah Tampala methanol and ethanol extract (1.56%, 3.175%, 6.25%, 12.5%, 25%, 50%, and 100%) was tested for antifungal potency using dilution method. The extract that could inhibit the growth of Candida albicans colonies was continued with the concentration density (35%, 37.5%, 40%, 42.5%, 45%, 47.5%, and 50%) in order to determine the Minimum Inhibitory Concentration (MIC) and Minimum Killing Concentration (MKC) by counting the number of colonies. Results: The methanol extract of Bajakah Tampala contains flavonoids, tannins, phenol, and saponin. In contrast, no flavonoids were detected in the ethanol extract. Candida albicans colonies were not inhibited by concentrations of 1.56%, 3.125%, 6.25%, 12.5%, and 25% in ethanol and methanol extracts, respectively. At concentrations of 50% and 100%, methanol extract inhibits colony growth, but ethanol extract is still growing. The antifungal activity of methanol extract showed a MIC of 35% and a MKC of 47.5%, as measured by its concentration density. Conclusion: Flavonoids are present in the Bajakah Tampala methanol extract, which inhibits and kills the growth of Candida albicans but not ethanol.